Lithium manganese iron phosphate material, preparation method thereof, positive pole piece and lithium ion battery
By adopting the preparation method of lithium manganese iron phosphate material with core-shell structure, the segregation and local overconcentration of manganese and iron are solved, the reduction of manganese dissolution amount and the improvement of electrochemical performance are achieved, and the electrical performance of lithium-ion batteries is significantly improved. and security and stability.
Patent Information
- Application Number
- CN202411476928.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-07
AI Technical Summary
During the preparation process, the segregation between manganese and iron is serious, resulting in poor conductivity and poor electrical performance. Locally over-concentrated during the precipitation reaction is prone to produce heterogeneous phases, affecting the phase purity and particle size distribution.
A core-shell structure preparation method of lithium manganese iron phosphate material is adopted. By controlling the reaction conditions and adding carbon layers, the manganese element is located outside the core, the lithium ion migration distance is shorter, and the electrolyte is more infiltrated, thereby reducing manganese dissolution and improving Electrochemical properties.
The manganese dissolution amount is significantly reduced, the powder resistivity and electrochemical performance are improved, so that lithium-ion batteries show higher charge and discharge rates and efficiency, and have better safety and stability.
Smart Images

Figure CN119400818A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a lithium iron manganese phosphate material, a preparation method thereof, a positive electrode sheet and a lithium-ion battery. Background Art
[0002] Lithium-ion battery is a rechargeable battery that uses lithium ions to move between positive and negative electrodes to store and release energy. Lithium-ion batteries have been widely used in the field of new energy vehicles due to their high energy density, long life and low self-discharge rate.
[0003] There are many kinds of cathode materials commonly used in lithium-ion batteries, mainly lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, ternary materials, lithium iron phosphate, etc. Among them, phosphate lithium-embedded materials with olivine crystal structure, such as LiMPO4 (M: Mn, Fe, Co, Ni), have become very potential cathode materials for lithium-ion batteries. The charging and discharging platform of lithium iron phosphate (LiFePO4) is very stable, and the structure is stable during the charging and discharging process. At the same time, it is non-toxic, pollution-free, and can be used in high temperature environments. The raw materials used in its preparation are widely available, and it has good electrochemical properties when used. It is currently the largest type of cathode material for lithium-ion batteries.
[0004] However, with the development of lithium iron phosphate, its performance improvement has encountered a bottleneck. On this basis, the lithium manganese iron phosphate positive electrode material formed by introducing manganese has a higher voltage platform and energy density. However, the current mainstream process of lithium manganese iron phosphate is still the solid phase process. The commonly used precursors are iron phosphate and manganese oxides. However, during the preparation process, the mutual mixing and solid phase fusion between the two are relatively poor, resulting in serious segregation of manganese and iron. The conductivity of the resulting lithium manganese iron phosphate is extremely poor, and the electrical performance is not easy in the manganese-rich area. At the same time, during the precipitation reaction, due to the K of the intermediate product ferrous manganese phosphate sp The pH value required for precipitation is relatively large. In the case of high pH value, the reaction system is prone to local over-concentration, so that part of the ferrous ions are precipitated as hydroxide, resulting in the formation of impurities in ferrous manganese phosphate, and further affecting the phase purity of the final lithium iron manganese phosphate material. In addition, due to the phenomenon of local over-concentration in the above-mentioned preparation process, the nucleation and crystallization process of lithium iron manganese phosphate and its intermediates will also be affected, thereby affecting the particle size distribution and size uniformity of the lithium iron manganese phosphate product, and ultimately causing its electrochemical performance in lithium-ion battery electrodes to be poor.
[0005] In view of this, how to provide a lithium manganese iron phosphate material with low manganese segregation so that it can exhibit higher electrochemical performance when used as a positive electrode active material for lithium-ion batteries is one of the important technical problems that need to be solved in this field. Summary of the invention
[0006] In view of the technical problems existing in the background technology, the present application provides a lithium iron manganese phosphate material, a preparation method thereof, a positive electrode plate and a lithium ion battery, aiming to solve the technical problems in the prior art that the active material in the positive electrode plate of a lithium ion battery, i.e., the lithium iron manganese phosphate material, has serious manganese dissolution phenomenon and poor electrochemical performance.
[0007] In a first aspect, the present invention provides a lithium iron manganese phosphate material, wherein the core molecular formula of the lithium iron manganese phosphate material is Li x Mn y Fe 1-y (PO4) z , wherein 0.7≤x≤1.1, 0.15≤y<1, 0.9≤z≤1.05, the manganese dissolution amount of the lithium manganese iron phosphate material is 25ppm~33ppm, the powder resistivity is 12Ω·cm~28Ω·cm, and the amount of magnetic substance is 0.05ppm~0.12ppm.
[0008] The lithium iron manganese phosphate material powder provided by the present application has a small resistivity, a small amount of magnetic material, and significantly reduced manganese dissolution. When used as a positive electrode active material for a lithium ion battery, the corresponding lithium ion battery can exhibit a higher rate and efficiency of charging and discharging, thereby improving the electrical performance and safety stability of the lithium ion battery. And, the kernel of the present application is essentially a lithium iron manganese phosphate with a core-shell structure, in which the manganese element is located outside the kernel, because the migration distance of the external lithium is shorter and can be better infiltrated by the electrolyte, so the capacity of manganese can be better utilized. Correspondingly, the internal lithium iron phosphate has good conductivity, so it does not affect the overall capacity of the material, so that the electrical performance of the obtained lithium iron manganese phosphate material is particularly excellent.
[0009] In the technical solution of the preferred embodiment of the present application, the lithium iron manganese phosphate material includes a core and a carbon layer arranged on the surface of the core; the D50 particle size of the lithium iron manganese phosphate material is 1.35μm~1.9μm; based on the weight of the lithium iron manganese phosphate material as 100%, the mass fraction of the carbon layer is 1%~3%.
[0010] The lithium manganese iron phosphate material provided in the present application has a more uniform particle size, and the inner core phosphate and the outer layer carbon have a better coordination effect, so that it can show better electrochemical performance in lithium-ion batteries, so that the resulting lithium-ion battery has higher electrical performance and better safety and stability.
[0011] In some preferred embodiments, the molecular formula of the core of the lithium manganese iron phosphate material is Li x Mn y Fe 1-y (PO4) z In, 1≤(1-y) / y≤5.
[0012] In the lithium manganese iron phosphate material provided in the present application, the ratio of manganese and iron elements is suitable, and it has more coordinated electrochemical properties, so that the corresponding lithium-ion battery has better performance.
[0013] In the second aspect, an embodiment of the present application provides a method for preparing a lithium iron manganese phosphate material, which comprises: mixing an iron source with a phosphoric acid solution, performing a first reaction, and obtaining a ferrous dihydrogen phosphate solution; adding a manganese salt and a first alkali source to the ferrous dihydrogen phosphate solution, performing a second reaction, and obtaining a ferrous manganese phosphate slurry; adding a lithium salt and a second alkali source to the ferrous manganese phosphate slurry, performing a third reaction, and obtaining a first product after filtering and washing, obtaining a second product after slurrying and drying the first product, and obtaining a lithium iron manganese phosphate material after calcining the second product; the first alkali source and the second alkali source are urea.
[0014] Compared with the traditional solid phase method, the above preparation method can realize the core-shell structure of lithium manganese iron phosphate, in which the manganese element is located outside the inner core. Because the migration distance of the external lithium is shorter and it can be better infiltrated by the electrolyte, the capacity of manganese can be better exerted, and the internal lithium iron phosphate has good conductivity, so it does not affect its capacity, so that the electrical properties of the lithium manganese iron phosphate material are excellent. Specifically, a ferrous dihydrogen phosphate solution is first obtained through the first reaction; in the second reaction, the slow decomposition of urea is used to gradually increase the pH value of the reaction system, so that the ferrous ions and manganese ions are successively precipitated in the form of phosphate and the generation of ferrous hydroxide impurities is reduced, so that the mixing of manganese and iron elements is more uniform; the third reaction further utilizes urea decomposition, further slowly increases the pH value, and the lithium ions in the added lithium salt are further precipitated in the form of phosphate. Each reaction step cooperates to make the mixing of lithium, manganese, iron, and phosphorus more uniform, and obtain a lithium manganese iron phosphate material with better electrochemical performance.
[0015] In the technical scheme of the preferred embodiment of the present application, the molar ratio of the first alkali source to the ferrous dihydrogen phosphate in the ferrous dihydrogen phosphate solution is (2.2-2.5):1, so that when urea as the first alkali source decomposes to obtain ammonia and reacts with the hydrogen ions in the dihydrogen phosphate, it can better promote the pH value in the reaction system to gradually increase, thereby obtaining a lithium manganese iron phosphate material with higher purity and better electrochemical properties; preferably, the molar ratio of the second alkali source to the first alkali source is (0.3-0.6):1, so that the urea added to the reaction system twice can be better coordinated in terms of the added amount, thereby better controlling the change in the pH value of the system and obtaining a lithium manganese iron phosphate material with more excellent electrochemical properties.
[0016] In some preferred embodiments, the ratio of the molar amount of manganese in the manganese salt to the molar amount of iron in the ferrous dihydrogen phosphate solution is (0.2-1):1, and the ratio of the sum of the molar amount of manganese in the manganese salt and the molar amount of iron in the ferrous dihydrogen phosphate solution to the molar amount of lithium in the lithium salt is 1:(1.08-1.1), so as to form the above-mentioned core-shell structure, and obtain a lithium manganese iron phosphate material with a more stable structure and better cyclic performance in lithium ion batteries; preferably, the iron source is iron sheet and / or iron powder, the manganese salt is selected from one or more of manganese sulfate, manganese chloride and manganese acetate, and the lithium salt is selected from one or more of lithium sulfate, lithium chloride and lithium acetate. The use of the above-mentioned divalent manganese salt and iron salt can effectively save costs, reduce the introduction of impurities and the generation of waste gas during subsequent calcination, and ultimately significantly improve the purity of the material, so that it exhibits more stable long-cycle characteristics in lithium ion batteries.
[0017] In some preferred embodiments, the temperature of the first reaction is 50°C to 70°C, and the pH value of the ferrous dihydrogen phosphate solution is 2.0 to 2.5, so as to obtain a ferrous dihydrogen phosphate solution with higher purity, while improving its dispersibility to facilitate subsequent processes; preferably, the concentration of the phosphoric acid solution is 3 mol / L to 6 mol / L, so as to better dissolve the iron source and obtain a ferrous dihydrogen phosphate solution with better dispersibility, so as to promote the improvement of the uniformity of the particle size of the intermediate product and the final product.
[0018] In some preferred embodiments, the temperature of the second reaction is 95°C to 105°C, and the endpoint pH value of the second reaction is 4.5 to 5.5, so as to obtain an intermediate product with a more stable structure, with ferrous phosphate as the core and manganese phosphate as the shell; preferably, the second reaction also includes continuing the reaction for 30min to 60min after reaching the endpoint pH value of the second reaction, so that the coprecipitation reaction can proceed more fully, and the mixing uniformity of the elements in the structure of the intermediate product obtained above and the uniformity of the particle size of the intermediate product itself can be more significantly improved, so as to stabilize its chemical structure and improve its electrochemical performance, especially reduce the dissolution of manganese, and make its chemical properties more stable.
[0019] In some preferred embodiments, the second reaction is preferably carried out under the condition that the oxygen content is less than 100 ppm, so as to reduce the generation of oxygen-containing compound impurities during the reaction, improve the purity of the lithium manganese iron phosphate material, and ultimately make the electrical performance of the lithium ion battery prepared when it is used as the positive electrode active material more superior.
[0020] In some preferred embodiments, the temperature of the third reaction is 100°C to 110°C, and the endpoint pH value of the third reaction is 7.1 to 7.5, so as to form a more uniform lithium phosphate on the surface of ferrous manganese phosphate, thereby more effectively inhibiting the dissolution of manganese in subsequent applications and improving its electrochemical properties, especially stability; preferably, the third reaction also includes continuing the reaction for 30 minutes to 60 minutes after reaching the endpoint pH value of the third reaction. Preferably, the third reaction is carried out under the condition that the oxygen content is less than 50 ppm, so as to further reduce impurities and improve the purity of the obtained lithium iron manganese phosphate material.
[0021] In some preferred embodiments, the method for preparing the lithium manganese iron phosphate material further includes: slurrying the first product to obtain a first product slurry, adding a carbon source to the first product slurry, and spray drying to obtain a second product. The present application further coats the surface of the lithium manganese iron phosphate material obtained above with a carbon source to further improve its structural stability and conductivity.
[0022] In some preferred embodiments, the solid content of the first product slurry is 30% to 40%, the particle size of the second product is 5 μm to 8 μm, and the mass fraction of water in the second product is less than or equal to 1%, so that the carbon layer coating is more uniform, and the particle size uniformity of the obtained material is controlled, so that it exhibits more stable electrochemical performance; preferably, the carbon source is a water-soluble carbon source, more preferably one or more of water-soluble starch, sucrose, glucose or polyethylene glycol. These carbon sources can cooperate with the above-mentioned lithium manganese iron phosphate core and form a more uniform and stable carbon layer on its surface, thereby effectively improving its electrochemical performance.
[0023] In some preferred embodiments, the calcination is carried out under the conditions of oxygen content less than 5ppm and humidity less than 3%, and the holding temperature is 700℃~750℃, and the holding time is 8h~15h. Calcination under such conditions can make the magnetic substance content in the obtained lithium manganese iron phosphate product lower and the electrochemical performance better.
[0024] In a third aspect, an embodiment of the present application provides a positive electrode plate, which includes the above-mentioned lithium iron manganese phosphate material, or the lithium iron manganese phosphate material prepared by the above-mentioned method for preparing the lithium iron manganese phosphate material. The positive electrode plate contains the above-mentioned lithium iron manganese phosphate material with low manganese dissolution, low powder resistivity and low magnetic material, and thus has higher electrochemical performance.
[0025] In a fourth aspect, the present application provides a lithium-ion battery, including the above-mentioned positive electrode sheet. Since the above-mentioned lithium manganese iron phosphate material obtained in the present application has both good electrochemical performance and structural stability, when it is used as a positive electrode sheet component in a lithium-ion battery, the obtained lithium-ion battery also has comprehensively improved electrochemical performance, especially the first charge capacity, the first discharge capacity and the first discharge efficiency.
[0026] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0028] Figure 1 This is a SEM result of the lithium manganese iron phosphate positive electrode material obtained in Example 1 of the present application;
[0029] Figure 2 This is the XRD spectrum of the lithium manganese iron phosphate positive electrode material obtained in Example 1 of the present application;
[0030] Figure 3 This is an EDS result diagram of the elemental composition of the lithium iron manganese phosphate positive electrode material obtained in Example 1 of the present application;
[0031] Figure 4 This is a SEM result of the lithium manganese iron phosphate positive electrode material obtained in Example 2 of the present application;
[0032] Figure 5 The XRD patterns of the lithium iron manganese phosphate positive electrode materials obtained in Examples 2 and 3 of the present application;
[0033] Figure 6 This is a SEM result of the lithium manganese iron phosphate positive electrode material obtained in Example 3 of the present application;
[0034] Figure 7 This is a process flow chart of the method for preparing lithium manganese iron phosphate material provided in an embodiment of the present application. DETAILED DESCRIPTION
[0035] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0037] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0038] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0039] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0040] As described in the background art, the active material in the positive electrode plate of lithium-ion batteries in the prior art, namely, lithium manganese iron phosphate material, has the problem of severe manganese dissolution and poor electrochemical performance.
[0041] In order to solve the above technical problems, in the first aspect, the embodiment of the present application provides a lithium iron manganese phosphate material, the core molecular formula of the lithium iron manganese phosphate material is Li x Mn y Fe 1-y (PO4) z, wherein 0.7≤x≤1.1, 0.15≤y<1, 0.9≤z≤1.05; the manganese dissolution amount of the lithium manganese iron phosphate material is 25ppm~33ppm, the powder resistivity is 12Ω·cm~28Ω·cm, and the amount of magnetic substance is 0.05ppm~0.12ppm.
[0042] The lithium iron manganese phosphate material powder has a low resistivity. When used as a positive active material for a lithium ion battery, it can make the corresponding lithium ion battery show a higher charge and discharge rate and efficiency, thereby improving the overall performance of the lithium ion battery. At the same time, the amount of magnetic substances in the obtained lithium iron manganese phosphate material is lower, which is beneficial to the safety performance of lithium iron manganese phosphate, so that the final prepared battery cell is safer and has a lower self-discharge. Specifically, reducing gas is generated during the calcination process of lithium iron manganese phosphate, which has a reducing effect on manganese and iron elements in the material, and when reduced, the electronic configuration of iron and manganese will change. The number of unpaired electrons of iron will increase, and the magnetism will be enhanced; while the number of unpaired electrons of manganese is relatively small, but its magnetism will still be enhanced. When the content of these two magnetic substances increases, it can make it easy to be corroded by the electrolyte, produce metal deposition under electrochemical action, thereby causing black spots on the diaphragm, affecting the cycle performance, safety performance and self-discharge of the battery cell.
[0043] The lithium manganese iron phosphate material provided in the present application has a manganese dissolution amount of 25ppm to 33ppm, that is, manganese dissolution is significantly reduced, which is conducive to maintaining the structural stability of the positive electrode material, thereby improving the cycle life of the battery, and can also reduce the phase change of the positive electrode material during the charging and discharging process, thereby improving the capacity retention rate of the battery. This means that after a long period of use, the battery has a small capacity loss and can maintain a high energy density. In particular, manganese dissolution may cause the lattice structure of the material to be destroyed, thereby affecting the normal deintercalation of lithium ions during the charging and discharging process. Therefore, the reduction in manganese dissolution helps the positive electrode material maintain the structural integrity of the material, thereby improving its thermal stability. Thermal stability is very important for the safety performance of the battery, especially in a high temperature environment. Batteries with good thermal stability are less prone to thermal runaway and have better safety performance. At the same time, manganese dissolution can cause manganese to be deposited on the diaphragm under electrochemical action, so that it is easy to pierce the diaphragm and cause a micro-short circuit in the battery cell.
[0044] In the technical solution of the preferred embodiment of the present application, the lithium iron manganese phosphate material includes a core and a carbon layer arranged on the surface of the core; the D50 of the lithium iron manganese phosphate material is 1.35μm to 1.9μm; the mass fraction of the carbon layer is 1% to 3% based on the weight of the lithium iron manganese phosphate material as 100%. The lithium iron manganese phosphate material provided by the present application has a more uniform particle size, and the coordination effect between the core phosphate and the outer layer carbon is better, so that it can show better electrochemical performance in the lithium ion battery, so that the obtained lithium ion battery has higher electrical performance and better safety and stability.
[0045] In some preferred embodiments, the molecular formula of the lithium manganese iron phosphate material is Li x Mn y Fe 1-y (PO4) z , 1≤(1-y) / y≤5. In the lithium manganese iron phosphate material provided in the present application, each element is appropriately proportioned and has more coordinated electrochemical properties, so that the corresponding lithium ion battery has better performance.
[0046] In particular, the phosphate core provided by the present application is essentially a lithium manganese iron phosphate with a core-shell structure, wherein the manganese element is located outside the core, because the migration distance of the lithium outside is shorter and it can be better infiltrated by the electrolyte, so the capacity of manganese can be better utilized. Accordingly, the internal lithium iron phosphate has good conductivity, so it does not affect the overall capacity of the material, so that the electrical properties of the obtained lithium manganese iron phosphate material are particularly excellent.
[0047] In the second aspect, an embodiment of the present application provides a method for preparing a lithium iron manganese phosphate material, which comprises: mixing an iron source with a phosphoric acid solution, performing a first reaction, and obtaining a ferrous dihydrogen phosphate solution; adding a manganese salt and a first alkali source to the ferrous dihydrogen phosphate solution, performing a second reaction, and obtaining a ferrous manganese phosphate slurry; adding a lithium salt and a second alkali source to the ferrous manganese phosphate slurry, performing a third reaction, and obtaining a first product after filtering and washing, obtaining a second product after slurrying and drying the first product, and obtaining a lithium iron manganese phosphate material after calcining the second product; the first alkali source and the second alkali source are urea.
[0048] The above-mentioned preparation method provided by the present application first prepares ferrous manganese phosphate by homogeneous precipitation method, that is, first prepares ferrous dihydrogen phosphate by adding iron and phosphoric acid, then sequentially mixes ferrous salt and manganese salt, and simultaneously supplements with urea, and urea is decomposed in the reaction to obtain ammonia gas and react with hydrogen ions in dihydrogen phosphate, so that the pH gradually rises, avoids local overconcentration, and finally obtains ferrous manganese phosphate with a purer phase and more uniform particle size, in which case ferrous phosphate is the core and manganese phosphate grows on the surface of ferrous phosphate. Then lithium salt and urea are mixed, so that uniform lithium phosphate can be formed on the surface of ferrous manganese phosphate. In the reaction process, the different pH characteristics of the phosphate precipitation of manganese, ferrous iron and lithium are used, that is, first at a lower pH, the pH is gradually increased through the slow decomposition of urea, and then the iron and manganese are first precipitated in the form of phosphate, and then lithium salt is added, and then urea is continued to be added, and the temperature is continued to rise, and the pH is controlled to rise further, so that the lithium element is also precipitated in the form of phosphate. Due to the factors of homogeneous precipitation and urea decomposition rate, the precipitate will be precipitated preferentially by heterogeneous nucleation to form a uniformly mixed co-precipitation of lithium, manganese, iron and phosphorus, and then it is slurried, dried and calcined in sequence to obtain a manganese iron phosphate lithium material with low manganese dissolution, powder resistivity and the amount of magnetic substances. Its electrochemical performance is more excellent. After being applied to lithium-ion batteries, the performance of the battery is significantly improved.
[0049] The above-mentioned preparation method, compared with the traditional solid phase method, can realize the lithium manganese iron phosphate of core-shell structure, the external manganese, because the migration distance of lithium is shorter, and it can be better infiltrated by the electrolyte, so it can better play the capacity of manganese, and the internal lithium iron phosphate, because of its good conductivity, does not affect its capacity, and the electrical properties of the final material are excellent. At the same time, the elements in the obtained material are evenly distributed, especially the ferromanganese elements are evenly arranged, which avoids the segregation of the manganese element, so that the capacity of the material is higher, because the segregation of manganese alone will cause the aggregation of lithium manganese phosphate, and the ionic conductivity of lithium manganese phosphate is poor, and lithium cannot be taken out, resulting in a reduction in charging capacity and discharge capacity. And the material prepared by the preparation method provided in the present application, because the ferromanganese is evenly mixed, thereby avoiding the occurrence of the above situation, and then making the final prepared lithium ion battery capacity higher, and the subsequent cycle performance will also be more excellent.
[0050] And, the above method provided by the present application does not require mixing, grinding and other processes, that is, it can achieve uniform mixing of multiple elements such as manganese, iron, phosphorus, and lithium. Specifically, the preparation method provided by the present application successfully achieves uniform mixing between the elements in the lithium iron manganese phosphate material through two co-precipitation steps performed in sequence, namely the second reaction and the third reaction, and obtains a positive electrode material with a more complete and stable lattice structure. The conventional solid-phase method requires mixing, slurrying, grinding and nano-sizing, and its process flow is long and the mixing effect is not good. In comparison, the preparation method of the lithium iron manganese phosphate material provided by the present application has a simpler process and better mixing effect. At the same time, the preparation method of lithium manganese iron phosphate material provided by the present application, compared with the traditional process, lacks oxidation, drying, grinding and other processes. According to actual calculations, the cost of these process steps is about 4,000 yuan. Adding the reduced cost of oxidants and carbon reduction, it can be roughly estimated that the cost per ton of product (lithium manganese iron phosphate) is reduced by 4,300 yuan / ton compared with the traditional solid-phase method. Calculated based on an annual production line of 10,000 tons, the cost savings reach 43 million, which is of great economic value.
[0051] In the present application, the positive electrode material obtained by calcination is then crushed, sieved and packaged, and finally a positive electrode material that can be used as a product for practical application is obtained.
[0052] In the technical solution of the preferred embodiment of the present application, the molar ratio of the first alkali source to the ferrous dihydrogen phosphate in the ferrous dihydrogen phosphate solution is (2.2-2.5):1, so that when urea as the first alkali source decomposes to obtain ammonia and reacts with hydrogen ions in dihydrogen phosphate, it can better promote the pH in the reaction system to gradually increase, thereby obtaining a lithium manganese iron phosphate material with higher purity and better electrochemical performance. After a large number of experiments, the inventor further preferred the molar ratio of the second alkali source to the first alkali source to be (0.3-0.6):1, so that the urea added to the reaction system twice can be better matched in the amount of addition, so as to better control the change of the system pH and obtain a lithium manganese iron phosphate material with more excellent electrochemical performance.
[0053] In some preferred embodiments, in order to obtain a higher purity ferrous dihydrogen phosphate solution and improve its dispersibility for subsequent processes, the temperature of the first reaction is preferably 50°C to 70°C, and the pH value of the ferrous dihydrogen phosphate solution is 2.0 to 2.5. At the same time, the concentration of the phosphoric acid solution is preferably 3 mol / L to 6 mol / L, so that the iron source is better dissolved and a ferrous dihydrogen phosphate solution with better dispersibility is obtained, so as to promote the improvement of the uniformity of the particle size of the intermediate product and the final product.
[0054] In some preferred embodiments, the temperature of the second reaction is 95°C to 105°C, and the endpoint pH value of the second reaction is 4.5 to 5.5, so as to obtain an intermediate product with a more stable structure, ferrous phosphate as the core and manganese phosphate as the shell. Further, the inventors have preferred through a large number of experiments that the second reaction also includes continuing the reaction for 30min to 60min after reaching the endpoint pH value of the second reaction, so as to more significantly improve the uniformity of the particle size of the intermediate product obtained, stabilize its chemical structure, and thus improve its electrochemical performance, especially reduce the dissolution of manganese, and make its chemical properties more stable.
[0055] It should be noted that the endpoint pH value in this application means that the reaction is considered to be basically completed when the reaction system reaches a certain pH value. As for the reaction that continues for a period of time after the reaction reaches its endpoint pH value, it is still carried out at the same temperature and stirring speed.
[0056] In some preferred embodiments, in order to make the reaction proceed more fully, the stirring speed of the second reaction is preferably 60r / min to 120r / min, and then the intermediate product with higher particle size uniformity is obtained, which effectively optimizes the performance of the final lithium manganese iron phosphate material. The second reaction is preferably carried out under the condition that the oxygen content is less than 100ppm, thereby reducing the generation of oxygen-containing compound impurities during the reaction, improving the purity of the lithium manganese iron phosphate material, and ultimately making the electrical performance of the lithium ion battery prepared when it is used as a positive electrode active material more superior.
[0057] In some preferred embodiments, the temperature of the third reaction is 100°C to 110°C, and the endpoint pH value of the third reaction is 7.1 to 7.5. The inventors have optimized the experimental conditions through a large number of experiments to form a more uniform lithium phosphate on the surface of ferrous manganese phosphate, thereby more effectively inhibiting the dissolution of manganese in subsequent applications and improving its electrochemical properties, especially stability. In order to allow the reaction to form lithium phosphate to proceed more fully, the third reaction preferably also includes continuing the reaction for 30 minutes to 60 minutes after reaching the endpoint pH value of the third reaction. More preferably, the third reaction is carried out under the condition that the oxygen content is less than 50ppm, thereby further reducing impurities and improving the purity of the obtained lithium iron manganese phosphate material.
[0058] In some preferred embodiments, in order to better form the above core-shell structure and obtain a lithium manganese iron phosphate material with a more stable structure and better cyclic performance in lithium-ion batteries, the inventors have optimized the addition ratio of each element in the core and shell through a large number of experiments. Specifically, the ratio of the molar amount of manganese in the manganese salt to the molar amount of iron in the ferrous dihydrogen phosphate solution is preferably (0.2-1):1, and the ratio of the sum of the molar amount of manganese in the manganese salt and the molar amount of iron in the ferrous dihydrogen phosphate solution to the molar amount of lithium in the lithium salt is 1:(1.08-1.1). Preferably, the iron source is iron sheet and / or iron powder, the manganese salt is selected from one or more of manganese sulfate, manganese chloride and manganese acetate, and the lithium salt is selected from one or more of lithium sulfate, lithium chloride and lithium acetate. After a large number of experiments, the inventors preferably use divalent manganese salts, ferrous salts, etc., which does not require the addition of oxidants to synthesize iron phosphate during the preparation process as in traditional processes. At the same time, in the final calcination process, there is no need to consume additional carbon to reduce high-valent metal ions, thereby effectively saving costs, reducing the introduction of impurities and the generation of waste gas during subsequent calcination, and ultimately significantly improving the purity of the material, so that it exhibits more stable long-cycle characteristics in lithium-ion batteries.
[0059] In some preferred embodiments, the preparation method of the lithium manganese iron phosphate material further includes: slurrying the first product to obtain a first product slurry, adding a carbon source to the first product slurry, and drying to obtain a second product. The present application further coats the surface of the lithium manganese iron phosphate material obtained above with a carbon source to further improve its structural stability and conductivity.
[0060] And, preferably the drying is spray drying.
[0061] In some preferred embodiments, in order to make the carbon layer coating more uniform and improve the uniformity of the particle size of the obtained material so that it exhibits more stable electrochemical performance, the solid content of the first product slurry is preferably 30% to 40%, the particle size of the second product is 5μm to 8μm, and the mass fraction of water in the second product is less than or equal to 1%. The solid content here refers to the mass fraction of insoluble solid particles in the first product slurry. After a large number of experiments, the inventor further preferred that the carbon source is a water-soluble carbon source, more preferably one or more of water-soluble starch, sucrose, glucose or polyethylene glycol, so that the carbon source can cooperate with the above-mentioned lithium iron manganese phosphate core and form a more uniform and stable carbon layer on its surface, thereby effectively improving its electrochemical performance.
[0062] In some preferred embodiments, calcination is carried out under the conditions of oxygen content less than 5ppm, CO content less than 50ppm, hydrogen content less than 100ppm, and humidity less than 3%, and the heating rate is 300℃ / h~400℃ / h, the insulation temperature is 700℃~750℃, and the insulation time is 8h~15h. The inventors have conducted a large number of experiments and optimized the calcination conditions to obtain the above scheme. Calcination under this condition reduces the generation of additional waste gas (such as waste gas generated by decomposition of lithium salts, oxidation-reduction, etc.), except for the waste gas generated by the decomposition of the crystal water and carbon source of the material itself, thereby making the atmosphere in the furnace more stable (because the main components of the waste gas are H2O and CO2, which will react with the hot carbon at high temperature to generate H2, CO and other gases, thereby consuming the carbon and making the carbon coating incomplete, and the strong reducing property of the generated H2, CO and other gases may reduce the iron to a single state, thereby generating magnetic substances, causing safety risks such as micro-short circuits and dendrites in the battery), so that the magnetic substance content in the obtained lithium manganese iron phosphate product is lower and the electrochemical performance is better.
[0063] In a third aspect, an embodiment of the present application provides a positive electrode plate, which includes the above-mentioned lithium iron manganese phosphate material, or the lithium iron manganese phosphate material prepared by the above-mentioned method for preparing the lithium iron manganese phosphate material.
[0064] In this embodiment, the positive electrode plate contains the above-mentioned lithium manganese iron phosphate material with low manganese dissolution, low powder resistivity and low magnetic substance, and thus has higher electrochemical performance.
[0065] In a fourth aspect, an embodiment of the present application provides a lithium-ion battery, comprising the positive electrode plate as above.
[0066] In this embodiment, because the above-mentioned lithium manganese iron phosphate material obtained in the present application has both good electrochemical properties and structural stability, when it is used as a positive electrode plate component in a lithium-ion battery, the obtained lithium-ion battery also has comprehensively improved electrochemical properties, especially the first charge and discharge capacity and the first discharge efficiency.
[0067] 1. Preparation method
[0068] Example 1
[0069] Preparation of a lithium manganese iron phosphate material:
[0070] 1. Add 4.5 mol / L phosphoric acid solution to electrolytic iron powder, react until the end point pH is 2.3, the reaction temperature is 60°C, filter, and obtain ferrous dihydrogen phosphate solution;
[0071] 2. Add manganese acetate to the ferrous dihydrogen phosphate solution, and the ratio of the molar amount of iron in the ferrous dihydrogen phosphate solution to the molar amount of manganese in the added manganese acetate is 1:1, and then add urea, the molar amount of the added urea is 2.4 times the molar amount of ferrous dihydrogen phosphate, and stir the reaction in a sealed reactor protected by nitrogen. After nitrogen is introduced to make the oxygen content in the sealed reactor lower than 100 ppm, the temperature is increased to react, the stirring speed is 100 r / min, the temperature is 100° C., the endpoint pH is controlled to be 4.9, and the reaction is continued for 50 minutes under this condition to obtain ferrous manganese phosphate slurry;
[0072] 3. Continue to add urea and lithium chloride to the ferrous manganese phosphate slurry, the ratio of the molar amount of lithium in the added lithium salt to the sum of the molar amounts of the added ferrous salt and manganese salt is 1.09:1, the molar ratio of the added urea to the urea added in step 2 is 0.45:1, continue to maintain the temperature at 105°C for reaction, continue to introduce nitrogen during the reaction process so that the oxygen content in the sealed reactor is less than 50ppm, control the endpoint pH to 7.3, continue to react under this condition for 50min, then filter and wash, use pure water for washing, wash until the conductivity of the washing water is ≤200μS / cm and then stop washing to obtain the first product;
[0073] 4. The first product is added with pure water to be slurried, and the solid content of the slurry is 35wt% after slurrying, and then water-soluble starch is added as a carbon source (which is converted into a carbon layer during the subsequent calcination process), stirred and dissolved, and then spray-dried. The particle size of the sprayed material is 5.6μm, and the moisture content is controlled at ≤1wt%, to obtain a spray-dried material, i.e., the second product;
[0074] 5. The spray-dried material is placed in an atmosphere furnace for calcination. The calcination process is carried out under the protection of a nitrogen atmosphere. The heating rate is 350°C / h. The temperature is raised to 725°C and kept at this temperature for 12 hours. During the calcination process, nitrogen is continuously introduced into the furnace. At the same time, an external induced draft fan is used to extract the exhaust gas. The pressure in the furnace is 40Pa higher than the external atmospheric pressure. The oxygen content in the atmosphere furnace is maintained below 5ppm, the CO content is below 50ppm, the hydrogen content is below 100ppm, and the humidity is below 3%. The material temperature is then reduced to ≤100°C before discharging. The calcined material is crushed and then sieved through a 150-mesh ultrasonic vibrating screen. An electromagnetic iron remover is used for iron removal. The packaging process is vacuum packaged in a constant temperature and humidity room at a temperature of 20°C-25°C and a humidity of ≤10%. The mass fraction of the carbon layer is 1.85%, and the molecular formula of the inner core is Li 1.05 Mn 0.50 Fe 0.50 (PO4) 1.04 Lithium manganese iron phosphate material.
[0075] The process flow of the above preparation method is the same as Figure 7The SEM results of the obtained lithium manganese iron phosphate positive electrode material are shown in Figure 1 , XRD results are shown in Figure 2 .
[0076] During the SEM test, the obtained lithium manganese iron phosphate was cut into sections, and the EDS results of its elemental composition are shown in Figure 3 . Figure 3 Elements that cannot be shown due to overlapping numbers are marked with arrows.
[0077] From the above figure, we can see that the elements are evenly distributed, especially the ferromanganese elements are evenly distributed, which avoids the segregation of manganese elements, so that the capacity of the material is higher. Because the segregation of manganese alone will cause the aggregation of lithium manganese phosphate, the ionic conductivity of lithium manganese phosphate is very poor, and lithium cannot be removed, resulting in low charge and discharge capacity. However, this embodiment avoids this situation because the ferromanganese is evenly mixed, so the capacity is higher, and the subsequent cycle performance will also be relatively excellent.
[0078] Example 2
[0079] Preparation of a lithium manganese iron phosphate material:
[0080] 1. Add 3 mol / L phosphoric acid solution to electrolytic iron powder, react until the end point pH is 2, the reaction temperature is 50°C, filter, and obtain ferrous dihydrogen phosphate solution;
[0081] 2. Add manganese acetate to the ferrous dihydrogen phosphate solution, and the ratio of the molar amount of iron in the ferrous dihydrogen phosphate solution to the molar amount of manganese in the added manganese acetate is 1:0.8, and then add urea, the molar amount of the added urea is 2.5 times the molar amount of ferrous dihydrogen phosphate, and stir the reaction in a sealed reactor protected by nitrogen. After nitrogen is introduced so that the oxygen content in the sealed reactor is lower than 100 ppm, the temperature is increased to react, the stirring speed is 120r / min, the temperature is reacted at 95°C, the endpoint pH is controlled to be 5.5, and the reaction is continued for 30min under this condition to obtain ferrous manganese phosphate slurry;
[0082] 3. Continue to add urea and lithium chloride to the ferrous manganese phosphate slurry, wherein the ratio of the molar amount of lithium in the added lithium salt to the sum of the molar amounts of the added ferrous salt and manganese salt is 1.08:1, and the molar ratio of the added urea to the urea added in step (2) is 0.6:1, and continue to react at a temperature of 100° C., and continue to introduce nitrogen during the reaction process so that the oxygen content in the sealed reactor is less than 50 ppm, and the endpoint pH is controlled to be 7.5. Continue to react for 30 min under this condition, and then filter and wash, using pure water for washing, and stop washing after washing until the conductivity of the washing water is ≤200 μS / cm to obtain a first product;
[0083] 4. The first product is added with pure water to make a slurry, and the solid content of the slurry is 30wt% after slurrying, and then a mixture of glucose and water-soluble starch in a mass ratio of 1:1 is added as a carbon source (the carbon source is converted into a carbon layer during the subsequent calcination process), stirred and dissolved, and then spray-dried. The particle size of the sprayed material is 3μm, and the moisture content is controlled at ≤1wt%, to obtain a spray-dried material, i.e., the second product;
[0084] 5. The spray-dried material is placed in an atmosphere furnace for calcination. The calcination process is carried out under the protection of a nitrogen atmosphere. The heating rate is 300°C / h. The temperature is raised to 700°C and kept at this temperature for 15 hours. During the calcination process, nitrogen is continuously introduced into the furnace. At the same time, an external induced draft fan is connected to extract exhaust gas. The pressure in the furnace is 40Pa higher than the external atmospheric pressure. The oxygen content in the atmosphere furnace is maintained below 5ppm, the CO content is below 50ppm, the hydrogen content is below 100ppm, and the humidity is below 3%. The material temperature is then reduced to ≤100°C before discharging. The calcined material is crushed and then sieved through a 150-mesh ultrasonic vibrating screen. An electromagnetic iron remover is used for iron removal. The packaging process is vacuum packaged in a constant temperature and humidity room at a temperature of 20°C-25°C and a humidity of ≤10%. The carbon layer mass fraction is 2.96wt%, and the core molecular formula is Li 1.02 Mn 0.45 Fe 0.55 (PO4) 0.98 Lithium manganese iron phosphate material.
[0085] The SEM results of the obtained lithium manganese iron phosphate positive electrode material are shown in Figure 4 , XRD results are shown in Figure 5 .
[0086] Example 3
[0087] Preparation of a lithium manganese iron phosphate material:
[0088] 1. Add 6 mol / L phosphoric acid solution to electrolytic iron powder, react until the end point pH is 2.5, the reaction temperature is 50°C, filter, and obtain ferrous dihydrogen phosphate solution;
[0089] 2. Add manganese acetate to the ferrous dihydrogen phosphate solution, and the ratio of the molar amount of iron in the ferrous dihydrogen phosphate solution to the molar amount of manganese in the added manganese acetate is 1:0.2, and then add urea, the molar amount of the added urea is 2.2 times the molar amount of ferrous dihydrogen phosphate, and stir the reaction in a sealed reactor protected by nitrogen. After nitrogen is introduced so that the oxygen content in the sealed reactor is lower than 100 ppm, the temperature is raised to react, the stirring speed is 60 r / min, the temperature is reacted at 105° C., the endpoint pH is controlled to be 4.5, and the reaction is continued for 60 minutes under this condition to obtain ferrous manganese phosphate slurry;
[0090] 3. Continue to add urea and lithium chloride to the ferrous manganese phosphate slurry, wherein the ratio of the molar amount of lithium in the added lithium salt to the sum of the molar amounts of the added ferrous salt and manganese salt is 1.1:1, and the molar ratio of the added urea to the urea added in step (2) is 0.3:1, and continue to react at a temperature of 110° C., and continue to introduce nitrogen during the reaction process so that the oxygen content in the sealed reactor is less than 50 ppm, and the endpoint pH is controlled to be 7.1. Continue to react under this condition for 60 min, then filter and wash, use pure water for washing, and stop washing after washing until the conductivity of the washing water is ≤200 μS / cm to obtain a first product;
[0091] 4. The first product is added with pure water to be slurried, and the solid content of the slurry is 30wt% after slurrying, and then sucrose is added as a carbon source (which is converted into a carbon layer during the subsequent calcination process), stirred and dissolved, and then spray-dried. The particle size of the sprayed material is 8μm, and the moisture content is controlled at ≤1wt%, to obtain a spray-dried material, i.e., the second product;
[0092] 5. The spray-dried material is placed in an atmosphere furnace for calcination. The calcination process is carried out under the protection of a nitrogen atmosphere. The heating rate is 400°C / h. The temperature is raised to 750°C and kept at this temperature for 8 hours. During the calcination process, nitrogen is continuously introduced into the furnace. At the same time, an external induced draft fan is connected to extract the exhaust gas. The pressure in the furnace is 40Pa higher than the external atmospheric pressure. The oxygen content in the atmosphere furnace is maintained below 5ppm, the CO content is below 50ppm, the hydrogen content is below 100ppm, and the humidity is below 3%. The material temperature is then reduced to ≤100°C before discharging. The calcined material is crushed and then sieved through a 150-mesh ultrasonic vibrating screen. An electromagnetic iron remover is used for iron removal. The packaging process is vacuum packaged in a constant temperature and humidity room at a temperature of 20°C-25°C and a humidity of ≤10%. The carbon layer mass fraction is 1.06wt%, and the core molecular formula is Li 0.79 Mn 0.18 Fe 0.82 (PO4) 1.03 Lithium manganese iron phosphate material.
[0093] The SEM results of the obtained lithium manganese iron phosphate positive electrode material are shown in Figure 6 , XRD results are shown in the figure Figure 5 .
[0094] Example 4
[0095] Preparation of a lithium manganese iron phosphate material:
[0096] The difference between this embodiment and embodiment 1 is only in step 1, specifically:
[0097] 1. Add 2 mol / L phosphoric acid solution to electrolytic iron powder, react until the end point pH is 3.0, the reaction temperature is 80°C, filter, and obtain ferrous dihydrogen phosphate solution.
[0098] The remaining steps are consistent with those in Example 1.
[0099] Example 5
[0100] Preparation of a lithium manganese iron phosphate material:
[0101] The difference between this embodiment and embodiment 1 is only in step 1, specifically:
[0102] 1. Add 7 mol / L phosphoric acid solution to electrolytic iron powder, react until the end point pH is 1.5, the reaction temperature is 40°C, filter, and obtain ferrous dihydrogen phosphate solution.
[0103] The remaining steps are consistent with those in Example 1.
[0104] Example 6
[0105] Preparation of a lithium manganese iron phosphate material:
[0106] The difference between this embodiment and embodiment 1 is only in step 2, specifically:
[0107] 2. Add manganese acetate to the ferrous dihydrogen phosphate solution, and the ratio of the molar amount of iron in the ferrous dihydrogen phosphate solution to the molar amount of manganese in the added manganese acetate is 1:0.1, and then add urea, the molar amount of the added urea is twice the molar amount of ferrous dihydrogen phosphate, and stir the reaction in a sealed reactor protected by nitrogen. After nitrogen is introduced so that the oxygen content in the sealed reactor is lower than 100 ppm, the temperature is increased to react, the stirring speed is 150 r / min, the temperature is reacted at 110°C, the endpoint pH is controlled to be 4.0, and the reaction is continued for 70 minutes under this condition to obtain ferrous manganese phosphate slurry.
[0108] The remaining steps are consistent with those in Example 1.
[0109] Example 7
[0110] Preparation of a lithium manganese iron phosphate material:
[0111] The difference between this embodiment and embodiment 1 is only in step 2, specifically:
[0112] 2. Add manganese acetate to the ferrous dihydrogen phosphate solution, and the ratio of the molar amount of iron in the ferrous dihydrogen phosphate solution to the molar amount of manganese in the added manganese acetate is 1:1.2, and then add urea, the molar amount of the added urea is 3 times the molar amount of ferrous dihydrogen phosphate, and stir the reaction in a sealed reactor protected by nitrogen. After nitrogen is introduced so that the oxygen content in the sealed reactor is lower than 100 ppm, the temperature is increased to react, the stirring speed is 50r / min, the temperature is 90°C, the endpoint pH is controlled to be 6.0, and the reaction is continued for 20min under this condition to obtain ferrous manganese phosphate slurry.
[0113] The remaining steps are consistent with those in Example 1.
[0114] Example 8
[0115] Preparation of a lithium manganese iron phosphate material:
[0116] The difference between this embodiment and embodiment 1 is only in step 3, specifically:
[0117] 3. Continue to add urea and lithium chloride to the ferrous manganese phosphate slurry, wherein the ratio of the molar amount of lithium in the added lithium salt to the sum of the molar amounts of the added ferrous salt and manganese salt is 1.0:1, and the molar ratio of the added urea to the urea added in step (2) is 0.2:1, and continue to react at a temperature of 120°C. During the reaction, nitrogen is continuously introduced so that the oxygen content in the sealed reactor is less than 50 ppm, and the endpoint pH is controlled to be 7.0. Under this condition, the reaction is continued for 70 min, and then filtered and washed with pure water. Washing is stopped after washing until the conductivity of the washing water is ≤200 μS / cm to obtain the first product.
[0118] The remaining steps are consistent with those in Example 1.
[0119] Example 9
[0120] Preparation of a lithium manganese iron phosphate material:
[0121] The difference between this embodiment and embodiment 1 is only in step 3, specifically:
[0122] 3. Continue to add urea and lithium chloride to the ferrous manganese phosphate slurry, wherein the ratio of the molar amount of lithium in the added lithium salt to the sum of the molar amounts of the added ferrous salt and manganese salt is 1.2:1, and the molar ratio of the added urea to the urea added in step (2) is 0.8:1, and continue to react at a temperature of 90°C. During the reaction, nitrogen is continuously introduced so that the oxygen content in the sealed reactor is less than 50 ppm, and the endpoint pH is controlled to be 8.0. Under this condition, the reaction is continued for 20 min, and then filtered and washed. Washing with pure water is used. Washing is stopped after washing until the conductivity of the washing water is ≤200 μS / cm to obtain the first product.
[0123] The remaining steps are consistent with those in Example 1.
[0124] Example 10
[0125] Preparation of a lithium manganese iron phosphate material:
[0126] The difference between this embodiment and embodiment 1 is only in step 5, specifically:
[0127] 5. The spray-dried material was placed in an atmosphere furnace for calcination. The calcination process was carried out under nitrogen atmosphere protection. The heating rate was 250°C / h. The temperature was raised to 650°C and kept at this temperature for 18 hours. The conditions were then kept consistent with those in Example 1.
[0128] The remaining steps are consistent with those in Example 1.
[0129] Embodiment 11
[0130] Preparation of a lithium manganese iron phosphate material:
[0131] The difference between this embodiment and embodiment 1 is only in step 5, specifically:
[0132] 5. The spray-dried material was placed in an atmosphere furnace for calcination. The calcination process was carried out under nitrogen atmosphere protection. The heating rate was 450°C / h, and the temperature was raised to 800°C. The temperature was kept at this temperature for 6 hours, and then the conditions were kept consistent with those in Example 1.
[0133] The remaining steps are consistent with those in Example 1.
[0134] Comparative Example 1
[0135] Preparation of a lithium manganese iron phosphate material:
[0136] 1. Ferrous dihydrogen phosphate, manganese acetate, lithium chloride and water-soluble starch are mixed to obtain a solid material, wherein the molar ratio of iron element, manganese element and lithium element in the solid material is 0.5:0.5:1.09;
[0137] 2. The solid material is placed in an atmosphere furnace for calcination. The calcination process is carried out under the protection of a nitrogen atmosphere. The heating rate is 350°C / h. The temperature is raised to 725°C and kept at this temperature for 12 hours. During the calcination process, nitrogen is continuously introduced into the furnace. At the same time, an external induced draft fan is used to extract exhaust gas. The pressure in the furnace is 40Pa higher than the external atmospheric pressure. The oxygen content in the atmosphere furnace is maintained below 5ppm, the CO content is below 50ppm, the hydrogen content is below 100ppm, and the humidity is below 3%. The material temperature is then reduced to ≤100°C before discharging. The calcined material is crushed and then sieved through a 150-mesh ultrasonic vibrating screen. An electromagnetic iron remover is used for iron removal. The packaging process is vacuum packaged in a constant temperature and humidity room at a temperature of 20°C-25°C and a humidity of ≤10%. A lithium manganese iron phosphate material with a carbon layer mass fraction of 1.85% is obtained.
[0138] 2. Test Method
[0139] Lithium manganese iron phosphate material performance test
[0140] 1. Element content: obtained through ICP-OES test.
[0141] 2. Manganese dissolution: Add 1 g of the sample to be tested into 100 mL of deionized water, stir and dissolve at 25°C for 30 minutes, then filter. The manganese content in the filtrate is measured by ICP-OES, which is the manganese dissolution amount.
[0142] 3. Free lithium: refer to SJT 11794-2021, measured by automatic potentiometric titration.
[0143] 4. Magnetic material content: Weigh 100g of material, pour it into a plastic bottle with a lid, add 1000g of pure water, and then add 8000GS of magnet, protect the outside of the magnet with polytetrafluoroethylene, then close the lid, place the plastic bottle horizontally and rotate it at a speed of 10-20r / min. After rotating for 30-45min, stop rotating, take out the magnet, add 1000g of pure water, put it into the plastic bottle, close the lid, place the plastic bottle horizontally and rotate it at a speed of 10-20r / min. After rotating for 5-10min, stop rotating, take out the magnet, add aqua regia to dissolve it, measure the dissolved solution with ICP, make the volume constant, measure the nickel, chromium, copper, zinc and iron content therein, calculate the total mass of nickel, chromium, copper, zinc and iron, and divide it by the weight of the material to obtain the magnetic foreign matter content of the material.
[0144] 5. Moisture: Tested using the Karl Fischer (KF) method.
[0145] 6. D50: According to GB / T 19077, particle size analysis by laser diffraction method.
[0146] 7. BET: According to GB / T 19587, the gas adsorption BET method is used to determine the specific surface area of solid substances.
[0147] 8. Compacted density: Determine the compacted density of powder according to GB / T 24533.
[0148] 9. Tap density: Determination of tap density of powder according to GB / T 5162-2021.
[0149] 10. Powder resistivity: tested using the four-probe method at a pressure of 10 MPa.
[0150] Half-cell performance test: The positive electrode materials obtained from each embodiment and comparative example were used to prepare half-cell samples, and their first charge and discharge capacities and first discharge efficiencies at 0.2C were tested.
[0151] The results of the above tests are shown in Tables 1 to 4.
[0152] III. Analysis of test results of various embodiments and comparative examples
[0153] Table 1
[0154]
[0155]
[0156] Table 2
[0157] ppm Manganese dissolution Free lithium Magnetic material content Moisture Example 1 26.8 354 0.11 451 Example 2 31.6 278 0.09 567 Example 3 32.6 421 0.06 325 Example 4 27.3 347 0.10 447 Example 5 26.9 338 0.12 467 Example 6 27.1 312 0.11 408 Example 7 30.2 325 0.10 417 Example 8 29.5 311 0.12 617 Example 9 32.7 768 0.12 698 Example 10 32.3 427 0.09 499 Embodiment 11 27.1 398 0.12 411 Comparative Example 1 43.7 368 0.18 498
[0158] Table 3
[0159]
[0160]
[0161] Table 4
[0162]
[0163] It can be seen from the above results that the above embodiments of the present application achieve the preparation of lithium manganese iron phosphate material with low manganese dissolution, low magnetic material content and low powder resistivity. Specifically:
[0164] By comparing the embodiments with the comparative examples, it can be seen that the preparation method adopted in the present application is superior to the lithium manganese iron phosphate material prepared by the conventional solid phase method, and after the lithium ion battery is prepared as the positive electrode material, the corresponding lithium ion battery exhibits a higher first charge and discharge specific capacity and first efficiency.
[0165] By comparing Examples 1 to 3 with Examples 4 and 5, it can be seen that in the preparation process of the ferrous dihydrogen phosphate solution, the temperature of the first reaction is preferably 50°C to 70°C, the pH value of the ferrous dihydrogen phosphate solution is preferably 2.0 to 2.5, and the concentration of the phosphoric acid solution is preferably 3 mol / L to 6 mol / L, so that a ferrous dihydrogen phosphate solution with better dispersibility can be obtained, so as to promote the improvement of the uniformity of the particle size of the intermediate product and the final product, thereby obtaining a lithium iron manganese phosphate positive electrode material with better electrochemical performance.
[0166] By comparing Examples 1 to 3 with Examples 6 and 7, it can be seen that in the preparation process of ferrous manganese phosphate slurry, the molar ratio of the first alkali source to the ferrous dihydrogen phosphate in the ferrous dihydrogen phosphate solution is preferably (2.2-2.5):1, the molar ratio of the manganese element in the manganese salt to the molar ratio of the iron element in the ferrous dihydrogen phosphate solution is preferably (0.2-1):1, and at the same time, in the reaction, the temperature of the second reaction is preferably 95°C-105°C, the stirring speed is 60r / min-120r / min, the endpoint pH value of the second reaction is 4.5-5.5, and after reaching the endpoint pH value of the second reaction, the reaction is continued for 30min-60min, and a more stable structure can be obtained with ferrous phosphate as the core and manganese phosphate as the shell. The intermediate product, thereby improving the electrochemical properties of the final lithium iron manganese phosphate positive electrode material.
[0167] By comparing Examples 1 to 3 with Examples 8 and 9, it can be seen that in the process of preparing the first product from the ferrous manganese phosphate slurry, the ratio of the sum of the molar amount of manganese element in the manganese salt and the molar amount of iron element in the ferrous dihydrogen phosphate solution to the molar amount of lithium element in the lithium salt is preferably 1: (1.08-1.1), and the molar amount ratio of the second alkali source to the first alkali source is (0.3-0.6): 1. At the same time, during the reaction process, the temperature of the third reaction is preferably 100°C-110°C, the endpoint pH value of the third reaction is 7.1-7.5, and after reaching the endpoint pH value of the third reaction, the reaction is continued for 30min-60min, which can promote the urea added to the reaction system twice to be better matched in the addition amount, thereby better controlling the change of the pH value of the system, and obtaining a manganese iron lithium phosphate material with more excellent electrochemical performance.
[0168] By comparing Examples 1 to 3 with Examples 10 and 11, it can be seen that in the process of finally calcining to obtain the lithium iron manganese phosphate material, the preferred calcination heating rate is 300°C / h to 400°C / h, the insulation temperature is 700°C to 750°C, and the insulation time is 8h to 15h, which can more effectively inhibit the generation of gases such as H2 and CO, thereby better protecting the integrity of the carbon coating layer and reducing the generation of magnetic substances, so that the content of magnetic substances in the obtained lithium iron manganese phosphate product is lower and the electrochemical performance is better.
[0169] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A lithium manganese iron phosphate material, characterized in that: The molecular formula of the core of the lithium manganese iron phosphate material is Li x Mn y Fe 1-y (PO4) z , wherein 0.7≤x≤1.1, 0.15≤y<1, 0.9≤z≤1.05; the manganese dissolution amount of the lithium manganese iron phosphate material is 25ppm~33ppm, the powder resistivity is 12Ω·cm~28Ω·cm, and the amount of magnetic substance is 0.05ppm~0.12ppm.
2. The lithium iron manganese phosphate material according to claim 1, characterized in that: The lithium iron manganese phosphate material further includes a carbon layer disposed on the surface of the core; The D50 particle size of the lithium manganese iron phosphate material is 1.35 μm to 1.9 μm; Based on the weight of the lithium manganese iron phosphate material being 100%, the mass fraction of the carbon layer is 1% to 3%.
3. The lithium iron manganese phosphate material according to claim 1 or 2, characterized in that: The molecular formula of the core of the lithium manganese iron phosphate material is Li x Mn y Fe 1-y (PO4) z In, 1≤(1-y) / y≤5.
4. A method for preparing lithium manganese iron phosphate material, characterized in that: The preparation method of the lithium manganese iron phosphate material comprises: The iron source is mixed with the phosphoric acid solution to perform a first reaction to obtain a ferrous dihydrogen phosphate solution; adding a manganese salt and a first alkali source to the ferrous dihydrogen phosphate solution to carry out a second reaction to obtain ferrous manganese phosphate slurry; A lithium salt and a second alkali source are added to the ferrous manganese phosphate slurry to carry out a third reaction, and a first product is obtained after filtering and washing. The first product is slurried and dried to obtain a second product, and the second product is calcined to obtain the lithium iron manganese phosphate material; the first alkali source and the second alkali source are urea.
5. The method for preparing lithium iron manganese phosphate material according to claim 4, characterized in that: The molar ratio of the first alkali source to the ferrous phosphate in the ferrous phosphate solution is (2.2-2.5):1; Preferably, the molar ratio of the second alkali source to the first alkali source is (0.3-0.6):1; Preferably, the ratio of the molar amount of manganese in the manganese salt to the molar amount of iron in the ferrous dihydrogen phosphate solution is (0.2-1):1, and the ratio of the sum of the molar amount of manganese in the manganese salt and the molar amount of iron in the ferrous dihydrogen phosphate solution to the molar amount of lithium in the lithium salt is 1:(1.08-1.1); More preferably, the iron source is iron sheet and / or iron powder, the manganese salt is selected from one or more of manganese sulfate, manganese chloride and manganese acetate, and the lithium salt is selected from one or more of lithium sulfate, lithium chloride and lithium acetate.
6. The method for preparing the lithium iron manganese phosphate material according to claim 4 or 5, characterized in that: The temperature of the first reaction is 50°C to 70°C, and the pH value of the ferrous dihydrogen phosphate solution is 2.0 to 2.5; Preferably, the concentration of the phosphoric acid solution is 3 mol / L to 6 mol / L.
7. The method for preparing the lithium iron manganese phosphate material according to any one of claims 4 to 6, characterized in that: The temperature of the second reaction is 95°C to 105°C, and the endpoint pH value of the second reaction is 4.5 to 5.5; Preferably, the second reaction further comprises continuing the reaction for 30 min to 60 min after reaching the endpoint pH value of the second reaction; Preferably, the second reaction is carried out under the condition that the oxygen content is less than 100 ppm.
8. The method for preparing the lithium iron manganese phosphate material according to any one of claims 4 to 7, characterized in that: The temperature of the third reaction is 100° C. to 110° C., and the endpoint pH value of the third reaction is 7.1 to 7.5; Preferably, the third reaction further comprises continuing the reaction for 30 min to 60 min after reaching the endpoint pH value of the third reaction; Preferably, the third reaction is carried out under the condition that the oxygen content is less than 50 ppm.
9. The method for preparing lithium iron manganese phosphate material according to any one of claims 4 to 8, characterized in that: The method for preparing the lithium manganese iron phosphate material further includes: slurrying the first product to obtain a first product slurry, adding a carbon source to the first product slurry, and spray drying to obtain the second product; Preferably, the solid content of the first product slurry is 30% to 40%; the particle size of the second product is 5 μm to 8 μm, and the mass fraction of water in the second product is less than or equal to 1%; Preferably, the carbon source is a water-soluble carbon source, more preferably one or more of water-soluble starch, sucrose, glucose or polyethylene glycol.
10. The method for preparing the lithium iron manganese phosphate material according to any one of claims 4 to 9, characterized in that: The calcination treatment is carried out under the conditions of oxygen content less than 5ppm and humidity less than 3%, and the insulation temperature of the calcination treatment is 700°C to 750°C, and the insulation time of the calcination treatment is 8h to 15h.
11. A positive electrode sheet, characterized in that: The positive electrode plate comprises the lithium iron manganese phosphate material according to any one of claims 1 to 3, or the lithium iron manganese phosphate material prepared by the method for preparing the lithium iron manganese phosphate material according to any one of claims 4 to 10.
12. A lithium ion battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 11.